Pendampingan Digitalisasi Produk Peternakan Ayam Petelur - Lahuri, Setiawan Bin; Sup, Devid Frastiawan Amir; Hibatullah, Lutfhi Ilham; Maylaffasya, Ghiyatska Shairafi; Khamid, Mohammad Abdul; Winarno, Rivaniansyah Siacahyo; Yahya, Ahmad; Putra, Rafif Mulana; Tajudin, Hafidh; Nawawi, Barkaa Alhudaebi; Rizky, Al Dihan Fiery; Handoko, Gesang Dwi (LP3M IAIFA Kediri, 2024)
In this era full of digitalization, there are still some business actors who still use traditional marketing techniques, where these techniques have a very tight level of competition with modern marketing techniques using digital media, so that if a business actor is unable or fails to compete with other business actors, it will cause them to be slowly eliminated from the market. This also happened to our partner, namely UD. Fajar Mulya. Although currently competition in the chicken egg market is not as fierce as in the vegetable market, it does not rule out the possibility that something similar will happen one day. The method used is the assistancing method, refer to approaches or strategies used to provide guidance, support, and assistance to UD. Fajar Mulya in achieving goals or overcoming problems in the form of digitizing laying chicken farming products. The results obtained after assistancing, currently UD. Fajar Mulya has a logo, print media (banners), social media, profile videos, and geographical indications. This assistance is carried out because, even though a business sector has great potential, if it cannot keep up with current developments, it is possible that it will lose out to other competitors.